Computational assessment of drug−induced effects on the electrocardiogram: from ion channel block to body surface potentials - Zemzemi, N; Bernabeu, M; Saiz, J; Cooper, J; Pathmanathan, P; Mirams, G; Pitt−Francis, J; Rodriguez, B (2013)
Background and purpose This work is based on the computational models describing the physiology of the electrical wave propagation in the heart. The goal is to show the ability of computational models to reproduce the effect drugs on the electrical activity of the heart at the cell, the organ (heart) and the ECG body surface potential levels. Experimental approach We use the state-of–the-art mathematical models governing the heart electrical activity. The drug model is introduced using an ion channel conductance block for both hERG and sodium depending on the IC50 value and the drug dose. We measure the ECG at the surface and compare the different biomarkers. Key results Introducing a 50% hERG block results in 7.8% prolongation of the APD90 and 5.7% QT interval prolongation, whereas the hERG block does not affect the QRS interval. Introducing 50% of sodium block prolongs the QRS and the QT intervals respectively by 12% and 5% and delays the activation times, whereas the sodium block does not affect the APD90. Conclusions and Implications Both potassium and sodium blocks prolong the QT interval, but the reason behind is different: For the first it is due to APD prolongation, while for the second it is due to a reduction of the electrical wave velocity. This example of study shows the usability of the in silco models in the investigation of drugs mechanism and the assessment of drug side effects.